1997
DOI: 10.1093/clinchem/43.12.2345
|View full text |Cite
|
Sign up to set email alerts
|

7α-Biotinylated testosterone derivatives as tracers for a competitive chemiluminescence immunoassay of testosterone in serum

Abstract: Ring core-biotinylated testosterone tracers were synthesized with bridges of three different lengths connecting the biotin moiety to the steroid core (7α-Cn-Bio-T, n = 3, 6, or 11). Together with a position 7-specific polyclonal anti-testosterone antibody, we used the 7α-C11-Bio-T tracer to develop a novel, labeled-hapten competitive immunoassay for total testosterone in serum. (The C3 and C6 tracers proved to be not suitable for analogous immunoassays.) Enhanced chemiluminescence signal was generated by use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…The stereochemistry of the 7R-C-linked epimers was established on the basis of 1 H and 13 C-experiments (DEPT, COSY, NOE, and decoupling experiments). The results are in accordance to spectroscopic data of other reported 7-substituted testosterone derivatives (Luppa et al, 1997). A characteristic proton-coupling pattern for the 6R,6β,7β-ABX system exhibited the R-stereochemistry of 7R-biotinylated T compounds.…”
Section: -Biotinylated T (Scheme 1)supporting
confidence: 90%
See 2 more Smart Citations
“…The stereochemistry of the 7R-C-linked epimers was established on the basis of 1 H and 13 C-experiments (DEPT, COSY, NOE, and decoupling experiments). The results are in accordance to spectroscopic data of other reported 7-substituted testosterone derivatives (Luppa et al, 1997). A characteristic proton-coupling pattern for the 6R,6β,7β-ABX system exhibited the R-stereochemistry of 7R-biotinylated T compounds.…”
Section: -Biotinylated T (Scheme 1)supporting
confidence: 90%
“…Recently, we showed that the introduction of a biotin label to E1 at the ring position 6R and to T at the position 7R leads to negligible alterations in comparison to the structure of the respective steroidal hapten (Luppa et al, 1994(Luppa et al, , 1996. These characteristics allow sensitive and reproducible determinations of E1 and T over large dynamic ranges (Luppa et al, 1995(Luppa et al, , 1997. In addition, the 7R-C 11 -Bio-T tracer, which we applied in the chemiluminescence immunoassay, provided higher specificity through a better availability of the critical antigen sites which is in accordance with suggestions made by Fra ´nek (1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology appeared to be more advantageous than conventional ELISA, in particular for the sensitivity [22] and stability. [23] To date, only biotinylated 7αtestosterone [24] 17α-ethinylestradiol, [23] and cortisol [25,26] were used as trappers in AB-ELISA. Furthermore, biotinylated steroids, if retaining their pristine biological activity, may be used in molecular biology as proteomic probes of biospecific interactions with their natural targets.…”
Section: Introductionmentioning
confidence: 99%
“…The linker group used to connect a label to a small molecule hapten or a macromolecule can have a profound influence on the performance of the bioconjugate. Linkers can contribute to “bridge-binding” interactions ( ) between tracers and antibodies when the same linker is used both in the immunogen and tracer. In this phenomenon, the antibody recognizes the commonly used linker in addition to or to the exclusion of the hapten.…”
Section: Introductionmentioning
confidence: 99%